Estudio del Parlamento Inglés para incrementar la eficiencia y eficacia legislativa en Michoacán - Paredes Silva, Leticia Isabel (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The legislative function has great social and historical roots in Michoacán, remembering the Constituent Congress of 1814 in Apatzingán that promulgated the Constitutional Decree for the freedom of Mexican America. We also remember that in the ten years that the Political Constitution of the Free Federated State of Michoacán was in force from 1825 to 1835, the Local Constituent Congress and the first six Constitutional Legislatures enacted 569 legal provisions of diverse hierarchy in the matters of their competence at an average 57 legislative provisions per year. In the course of history, to the date of preparation of this legal investigation there have been seventy-four Constitutional Legislatures in the State of Michoacán. Of them, forty-four established from 1825 to 1944, lasted two years and twenty-one from 1944 to 2008 three years. In addition, another six constitutional legislatures have had different periods of duration, namely: three legislatures in the first half of the 19th century lasted one year; one from the second half of the 19th century lasted four years and another one-year, and one so far in the 21st century, the LXXI Legislature lasted four years. Thus, we arrived at the LXXIV Legislature who had to face the onslaught of COVID 19, which affected the health of the whole world, made the brave decision not to stop the legislative function and continued the sessions through video conference, some for their importance were held in person, at the risk of the integrity of the legislators; some deputies were seriously damaged in their health.

La función legislativa tiene grandes raíces sociales e históricas en Michoacán, recordando el Congreso Constituyente de 1814 en Apatzingán que promulgo el Decreto Constitucional para la libertad de la América Mexicana. También recordamos que en los diez años que estuvo vigente la Constitución Política del Estado Libre Federado de Michoacán de 1825 a 1835, el Congreso Constituyente Local y las primeras seis Legislaturas Constitucionales promulgaron 569 disposiciones jurídicas de diversa jerarquía en las materias de su competencia a un promedio de 57 disposiciones en legislativas por año. En el curso de la historia, a la fecha de elaboración de esta investigación jurídica ha habido setenta y cuatro Legislaturas Constitucionales en el Estado de Michoacán. De ellas, cuarenta y cuatro establecidas de 1825 a 1944, tuvieron dos años de duración y veintiuno de 1944 a 2008 tres años. Además, otras seis legislaturas constitucionales han tenido diversos periodos de duración a saber: tres legislaturas de la primera mitad del siglo XIX duraron un año; una de la segunda mitad del siglo XIX duró cuatro años y otra un año, y una en lo que va del siglo XXI, la Legislatura LXXI duró cuatro años. Así, llegamos a la Legislatura LXXIV a quien le toco enfrentar los embates del COVID 19, que afecto la salud de todo el mundo, tomaron la valiente decisión de no detener la función legislativa y continuaron las sesiones por medio de video conferencia, algunas por su importancia se realizaron presenciales, a riesgo de la integridad de los legisladores; algunos diputados resultaron seriamente dañados en su salud.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2022-1407; Ciencias políticas; Eficiencia; Legislar; Prosperidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8527